Contemporary Insights into the Pharmacological Effects of Chalcones (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The chalcones constitute a group of α, β-unsaturated ketones that have attracted considerable attention within the field of medicinal chemistry because of the multiplicity of their pharmacological effects. These substances contain the structure of 1,3-diphenyl-2-propen-1-one, with α,β-unsaturated ketone moiety being responsible for their biological activity. The chalcones occur in nature as natural components of fruits, vegetables, tea, and soy foods; they are considered precursors of flavonoids and isoflavonoids. The derivatives of chalcones are known for exhibiting numerous pharmacological effects such as anticancer, anti-inflammatory, antimalarial, antidiabetic, antiviral, and anti-Alzheimer agents. Many natural chalcones and chalconoid preparations have also been used in traditional medicine.